TINJAUAN APLIKASI SISTEM INFORMASI AKUNTANSI - Rasmini, Mas; Suryanto, Suryanto (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2018)
This study aims to describe the application of accounting information systems related to recording financial statementscarried out by Multi-purpose Building Stores. The research method used in the study was descriptive with a qualitativeapproach. Data collection techniques used were in-depth interviews, observation, and documentation studies.Informants in this study are the owners of the company and employees who work as a recording of financial statements.Based on the results of the study that the application of accounting information systems can have a positive impactbecause it makes it simpler in preparing financial statements. The accounting information system application aims toimprove the quality of information, internal checks, and be able to reduce costs. In addition, accounting informationsystems are very useful in providing accurate and timely information. Several factors hinder the application ofaccounting information systems, namely human resources and technology.